VARIATION OF CROSS-EQUATORIAL NORTHERLY SURGE FORMATION CHARACTERISTICS AND ITS IMPACT ON RAINFALL IN THE WESTERN MARITIME CONTINENT - Nanda Purwadani, Narizka
Cross-equatorial northerly surge (CENS) is a synoptic-scale atmospheric phenomenon in the boreal winter season characterized by strong northerly winds from the South China Sea crossing the equator. This phenomenon could cause extreme rainfall in the northern part of western Java western. A known phenomenon that can trigger the formation of CENS is a cold surge (CS), but many CENS events are not triggered by CS. Therefore, this research will examine phenomena other than CS that can trigger CENS as well as identify the difference in the impact of rainfall in the western Maritime Continent caused between CENS triggered by CS (CENS-CS) and not triggered by CS (CENS-noCS). CENS-CS and CENS-noCS have different patterns of formation. Northerly wind anomalies in CENS-CS are caused by high-pressure propagation from extratropic, while northerly wind anomalies in CENS-noCS appear due to high-pressure anomalies around the equator. Based on the composite analysis of wind and pressure patterns, it was found that phenomena other than CS that could potentially trigger CENS are Madden Julian Oscillation (MJO) phases 6 and 7, Mixed Rossbygravity (MRG) phases 1 and 4 (dry and drying in the northern equator), and Equatorial Rossby (ER) phases 2 and 3 (moistening and wet). There are some differences in the impact of the rainfall in the western Maritime continent caused between CENS-CS and CENS-noCS. In the southern equator, CENS-CS causes wet anomalies along the northern part of Java Island to Nusa Tenggara, while CENS-noCS is only centralized around the northern part of western Java. Nevertheless, the rainfall in the northern part of western Java on CENS-noCS is stronger than on CENS-CS. In the northern equator, the CENS-CS has caused drought anomalies in Sumatera and the Malayan Peninsula and wet anomalies in western Kalimantan, while CENS-noCS causes drought anomalies in those three regions.